(untitled) (Ameghiniana, 2013)
A new species of Protocanites from the Lower Carboniferous rocks near Malimán, Prov. San Juan is described. The ocurrence of this ammonoid together with the presence of Tornoceras in rocks of Upper Devonian age lying unconformable under the Carboniferous formation may help in adjusting the Devonian-Carboniferous boundary in this part of the world.